Finite element analysis and bearing capacity calculation of cross-shaped CFST columns under compressive load - Mingjian Yang; Desun Yu; Qirong Qiu; Yong Yu (Heliyon, 2024)
The study investigated the load capacity of cross-shaped concrete-filled steel tubular (CFST) columns under axial and eccentric compression using finite element software ABAQUS. It analyzed six specimens with measured data and an additional 26 specimens with varied parameters, including eccentricity, slenderness ratio, section steel ratio and material properties such as concrete strength and steel yield strength.The objective was to understand how these parameters affect the load capacity of cross-shaped CFST columns. The research findings suggest that as eccentricity and slenderness ratio increase, the ultimate capacity decreases. Conversely, it increases with higher steel content, concrete strength and steel yield strength. Moreover, the bearing capacity deteriorates more rapidly with reduced eccentricity and concrete strength, while it demonstrates a nearly linear increase with greater steel content. Additionally, the study found that enhancing the resilience of the channel steel significantly boosts the load-bearing capacity of the column. Based on these findings, practical design equations were developed to determine the maximum bearing capacity of cross-shaped CFST columns under axial and eccentric compression. These equations are grounded in confined concrete theory and demonstrate robust applicability for practical design purposes.